Back to the Basics: Inferior Vena Cava Filters - Covello, Brian; Radvany, Martin (Seminars in Interventional Radiology, 2022)
Inferior vena cava filters are an important therapeutic option for patients with venous thromboembolism and contraindication to anticoagulation. Indications for filter placement have varied over the previous decades. This article discusses the history of inferior vena cava filter use, with a basic overview of technology and specific devices. Finally, this article reviews emerging filter design and technology. Understanding the basics of inferior vena cava filters is critical to building more robust clinical data for the purpose of improving patient outcomes.
Keywords: inferior vena cava filters; deep venous thrombosis; pulmonary embolism; interventional radiology